A study on the anti-skin tumor and anti-UVB damage effects of Gastrodia elata Bl. Products transformed by Armillaria mellea. Issue 1 (31st December 2022) - Zheng, Tong; Gao, Yugang; Zhang, Zhilong; Li, XinYue; Zang, Pu; Zhao, Yan; He, Zhongmei
ABSTRACT: Skin cancer is a malignant tumour that can spread in the skin and is a serious threat to human health. Excessive ultraviolet radiation is one of the most common factors that leads to skin cancer. The purpose of this study was to evaluate the anti-skin tumour and anti-UVB damage effects of Armillaria mellea (Vahl) P. Kumm transformed Gastrodia elata Bl products (ATGP). Gastrodia elata Blume f.glauca S. Chows from Changbai Mountain and 4 Armillaria mellea (Vahl) P. Kumm strains were used as experimental materials. First, the optimum fungal strains of Armillaria mellea used to transform gastrodin were screened. Then, the MTT assay and scratch test proved that ATGP had anti-B16 melanoma cell activity in vitro. Furthermore, the anti-UVB damage effect of ATGP was proven by a UVB damage mouse skin model and HaCat photoaging model, and its mechanism was preliminarily discussed. GRAPHICAL ABSTRACT: UF0001